The Effect of Intellectual Capital and Environmental, Social and Governance (ESG) Performance on Firm Value with Firm Suistanable Growth as a Moderation on Employee of Manufacturing Industry in Surabaya - GS, Achmad Daengs (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The purpose of this research is to analyze the influence of Intellectual Capital and Environmental, Social and Governance Performance on Firm Value moderated by Firm Sustainable Growth on Employee of Manufacturing Industry in Surabaya. Design/methodology/approach: This research was conducted to analyze whether there is an influence between independent and dependent variables. The study population was employees in the Manufacturing Industry in Surabaya. The sampling method used the theory of Hair et al., (2014) so sample of 100 employees in the Manufacturing Industry in Surabaya was obtained. The data collection technique was carried out by distributing research questionnaires. While the data analysis technique was through Partial Least Square analysis. Findings: The research results show that Intellectual Capital, ESG Performance, and Firm Sustainable Growth have a significant effect on Firm Value. Firm Sustainable Growth moderates the relationship between ESG Performance and Firm Value, but Firm Sustainable Growth does not moderate the relationship between Intellectual Capital and Firm Value. Research limitations/implications: This research was conducted at only one manufacturing company in Surabaya. Future research is expected to expand the intervening variables and expand the sample size. Paper type: Research paper